GPS Cinemático de precisión para la determinación de puntos en los aeropuertos (ING) - Moya Zamora, Jorge (2004)
The establishment of terrestrial support for aerial navigation is very important. Nowadays the use of Global Positioning System (GPS) is the most popular technique for aerial navigation as is it used in the determination of ground control points, which are used for the approximations of planes, their ladings and their locations on the bridges at airports. These networks must meet some norms which are regulated by the Organización de Aviación Civil Internacional (OACI). Their most important characteristics are the link to the World Geodetic System (WGS84), and the accuracy of the coordinates, which are fundamental to guarantee the activities of aerial navigation. In this article we present the kinematic GPS measurements in the establishment of this kind of points.